2015
DOI: 10.1038/srep11218
|View full text |Cite
|
Sign up to set email alerts
|

Distinct inter-hemispheric dysconnectivity in schizophrenia patients with and without auditory verbal hallucinations

Abstract: Evidence from behavioral, electrophysiological and diffusion-weighted imaging studies suggest that schizophrenia patients suffer from deficiencies in bilateral brain communication, and this disruption may be related to the occurrence of auditory verbal hallucinations (AVH). To increase our understanding of aberrant inter-hemispheric communication in relation to AVH, we recruited two groups of first-episode schizophrenia patients: one group with AVH (N = 18 AVH patients) and one without hallucinations (N = 18 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 67 publications
7
37
1
Order By: Relevance
“…The SZS group showed reduced connectivity in lateral connections from left to right IFG and from right to left A1 as compared to the NP patient group suggesting that such reductions are specific to schizophrenia spectrum disorders. This is in line with previous results as it is robustly found that schizophrenia is associated with an interhemispheric disconnection 3639 . Previous results on functional connectivity have shown that interhemispheric connectivity can distinguish schizophrenia patients from patients with depression, indicating specificity for schizophrenia 40 .…”
Section: Discussionsupporting
confidence: 93%
“…The SZS group showed reduced connectivity in lateral connections from left to right IFG and from right to left A1 as compared to the NP patient group suggesting that such reductions are specific to schizophrenia spectrum disorders. This is in line with previous results as it is robustly found that schizophrenia is associated with an interhemispheric disconnection 3639 . Previous results on functional connectivity have shown that interhemispheric connectivity can distinguish schizophrenia patients from patients with depression, indicating specificity for schizophrenia 40 .…”
Section: Discussionsupporting
confidence: 93%
“…Taking into account the more impaired sensory gating (i.e. inability to filter out irrelevant stimuli) in patients with a history of hallucination (Smith et al, 2013;Smucny et al, 2013) and differences in the connectivity of the DMN between AVH and NH subjects (Kindler et al, 2015;Chang et al, 2015), it is possible that eyes closure might have an effect in NH group but not in AVH group. Our results thus suggest that the hyperexcitability in AVH was not modified by general subjects' state.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Chang et al . [ 22 ] reported that the altered VMHC in the default mode network, inferior frontal gyrus, and cerebellum was associated with auditory hallucination symptoms, and aberrant VMHC in the sensorimotor region has been found only in schizophrenia patients experiencing nonauditory hallucination.…”
Section: Discussionmentioning
confidence: 99%